Effect of temperature on life history of Cirrospilus vittatus (Hymenoptera: Eulophidae), an ectoparasitoid of Phyllocnistis citrella (Lepidoptera: Gracillariidae) - Urbaneja, Alberto; Hinarejos, R.; Llácer, Elena; Garrido, Antonio; Jaques, Josep A. (2017)
Cirrospilus vittatus is a generalist parasitoid detected on the invading Phyllocnistis citrella 1 yr after the introduction of this pest into Spain in 1993. In this study, the influence of temperature on parasitoid development, survival, and some selected life history parameters was determined. Development times shortened as the temperature increased from 15 to 30 degrees C, but increased between 30 and 35 degrees C. Larval development times varied the greatest over the range of temperatures, whereas egg development varied the least. The estimated upper and lower development thresholds were 38.2 and 8.2 degrees C, respectively, and the maximal developmental rate (8.75 d(-1)) occurred at 31.5 degrees C. The thermal constant was 275.1 +/- 4.6 degree-days. Cirrospilus vittatus appeared to be a synovigenic species. Mean fecundity at 25 degrees C was 39.17 eggs per female, and the oviposition rate fluctuated around five eggs per day. Superparasitism was quite common (42.8%), but fertility was high (85.6%). Immature C. vittatus survival was 58.1%. From these results, an intrinsic rate of increase of 0.126 females per female per day was estimated. Although under typical Mediterranean climatic conditions, development of C. vittatus could continue throughout the year, its reproductive fitness at 25 degrees C is lower than other leafminer parasitoids attacking P. citrella in Spain. These results could account for the progressive displacement observed in field populations occurring between C. vittatus and the predominant indigenous parasitoids of P. citrella, Cirrospilus sp. near lyncus.